Method and device for predicting residual strength of ceramic matrix composite material

By finding the hysteresis modulus degradation model corresponding to the load stage, calculating the hysteresis modulus and fatigue life, combined with the fatigue degradation factor, the residual strength prediction of ceramic matrix composites under variable amplitude cyclic load is achieved, solving the problem that existing methods cannot accurately predict, and providing more accurate material damage status and design guidance.

CN119905184AActive Publication Date: 2025-04-29JINCHENG NANJING ELECTROMECHANICAL HYDRAULIC PRESSURE ENG RES CENT AVIATION IND OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510085522.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing ceramic matrix composite materials cannot accurately predict the residual strength prediction method under the amplitude cyclic load conditions, and it is difficult to characterize the damage state of the material under fatigue loads in real time, and it is impossible to effectively guide the design and application of the material.

Method used

By finding the hysteresis modulus degradation model corresponding to each load stage, the current hysteresis modulus is calculated, and the fatigue life and fatigue degradation factors are calculated based on the peak load value, failure probability and fatigue life correlation of the current load stage, and then the residual strength of the ceramic matrix composite material under the variable amplitude cycle load is predicted.

Benefits of technology

The accurate prediction of the residual strength of ceramic matrix composite materials under variable amplitude cyclic load conditions is achieved, which can more accurately reflect the damage state of the material under complex loads, and provide more effective design and application guidance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905184A_ABST
    Figure CN119905184A_ABST
Patent Text Reader

Abstract

The invention provides a method and a device for predicting residual strength of a ceramic matrix composite material. The residual strength prediction method of the ceramic-based composite material provided by the invention comprises the following steps: calculating a current hysteresis modulus according to a current cycle index and a target hysteresis modulus degradation model; determining a failure probability according to the peak load value, a preset failure stress and a predetermined static strength distribution function; calculating the fatigue life of the current load level according to the failure probability and the peak load value; determining a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction, the initial hysteresis modulus, the current fatigue life and the current cycle index; calculating an intensity attenuation value according to the peak load value, the residual intensity under the last cycle number and the fatigue degradation factor; and calculating the residual strength according to the peak load value and the strength attenuation value. According to the residual strength prediction method and device for the ceramic-based composite material, the residual strength of the ceramic-based composite material can be accurately predicted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a method and device for predicting the residual strength of a ceramic-based composite material. Background Art

[0002] With the continuous development of modern industrial technology, especially in the field of aerospace, the requirements for material performance are increasing. Ceramic Matrix Composites (CMCs) have become a very promising candidate material for high-temperature components of advanced aircraft engines due to their excellent high temperature resistance, high strength and light weight. Under extreme working environments, these materials are often subjected to complex and variable load conditions, among which variable amplitude cyclic loads are particularly common. However, variable amplitude fatigue performance, as an important indicator to measure the long-term working reliability of materials under complex loads, has always been a key factor restricting the widespread application of CMCs.

[0003] In the prior art, the prediction methods for residual strength are mainly focused on constant amplitude fatigue conditions. These methods provide an important basis for material life assessment and reliability design by predicting the fatigue damage accumulation and residual strength changes of materials under constant loads. However, since the fatigue damage mechanism of materials under variable amplitude cyclic loading conditions is more complex and the load sequence has a significant impact on the residual strength, the existing constant amplitude fatigue model cannot accurately predict the residual strength of ceramic matrix composites under variable amplitude scenarios, and it is difficult to characterize the damage state of materials under fatigue loads in real time, and it cannot effectively guide the design and application of materials. Summary of the invention

[0004] In view of this, the present application provides a method and device for predicting the residual strength of a ceramic matrix composite material, so as to accurately predict the residual strength of the ceramic matrix composite material.

[0005] Specifically, the present application is implemented through the following technical solutions:

[0006] In a first aspect, the present application provides a method for predicting the residual strength of a ceramic matrix composite material, the method being used to predict the residual strength of the ceramic matrix composite material under a variable amplitude cyclic load, the method comprising:

[0007] Searching for a target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels;

[0008] Calculating a current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model;

[0009] Determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function;

[0010] Calculating the fatigue life of the current load level according to the failure probability, the peak load value and a predetermined correlation between the fatigue life and the peak load value;

[0011] Determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the change law of the fatigue performance of the material from the degradation trend, the nonlinear characteristics and the stage characteristics during the loading process;

[0012] Calculate the strength attenuation value according to the peak load value of the current load level, the residual strength at the last cycle number and the fatigue degradation factor;

[0013] The residual strength of the ceramic matrix composite material at the current number of cycles is calculated according to the peak load value of the current load level and the strength attenuation value.

[0014] A second aspect of the present application provides a residual strength prediction device for a ceramic matrix composite material, the device comprising a search module, a calculation module, a determination module and a processing module; wherein:

[0015] The search module is used to search for a target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels;

[0016] The calculation module is used to calculate the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model;

[0017] The determination module is used to determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function;

[0018] The calculation module is used to calculate the fatigue life of the current load level according to the failure probability, the peak load value and the predetermined correlation between the fatigue life and the peak load value;

[0019] The processing module is used to determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the change law of the fatigue performance of the material from the degradation trend, the nonlinear characteristics and the stage characteristics during the loading process;

[0020] The calculation module is further used to calculate the strength attenuation value according to the peak load value of the current load level, the residual strength under the last cycle number and the fatigue degradation factor;

[0021] The calculation module is further used to calculate the residual strength of the ceramic-based composite material at the current number of cycles according to the peak load value of the current load level and the strength attenuation value.

[0022] The residual strength prediction method and device of ceramic matrix composite materials provided in the present application searches for the target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels, and then calculates the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model, and then determines the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function, and then calculates the fatigue life of the current load level according to the correlation between the failure probability, the peak load value and the predetermined fatigue life and the peak load value, and then determines the fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles, thereby calculating the strength attenuation value according to the peak load value of the current load level, the residual strength under the previous number of cycles and the hysteresis modulus degradation index, and according to the current The peak load value and strength attenuation value of the load level are used to calculate the residual strength of the ceramic matrix composite material under the current number of cycles. The current hysteresis modulus degradation model is found to be the pre-target, and then the current hysteresis modulus is calculated based on it. The current hysteresis modulus can be accurately calculated. In addition, when calculating the fatigue life of the current load level, the failure probability is introduced so that the calculation of the fatigue life can reflect the impact of the difference in load levels in actual working conditions on the life, and the fatigue life can be accurately calculated. Furthermore, on the basis of the above, the fatigue degradation factor is calculated according to the current hysteresis modulus, initial volume fraction, initial hysteresis modulus, fatigue life and current number of cycles. The fatigue degradation factor is used to quantify the material strength degradation at different cycle stages, and then the residual strength is predicted based on the fatigue degradation factor. In this way, through the coordinated cooperation of the above steps, the complex degradation behavior of the material under multi-level fatigue is decomposed, modeled and calculated, and the accurate prediction of the residual strength under variable amplitude load conditions is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of Example 1 of a method for predicting residual strength of a ceramic matrix composite material provided in the present application;

[0024] Figure 2 A schematic diagram of the hysteresis modulus shown as an exemplary embodiment of the present application;

[0025] Figure 3 A schematic diagram of a prediction result of residual strength shown in an exemplary embodiment of the present application;

[0026] Figure 4 A flow chart of Example 2 of a method for predicting residual strength of a ceramic matrix composite material provided in the present application;

[0027] Figure 5 A flowchart of Example 3 of the residual strength prediction method for ceramic matrix composite materials provided in this application;

[0028] Figure 6 A flowchart of a fourth embodiment of a method for predicting residual strength of a ceramic matrix composite material provided in the present application;

[0029] Figure 7 A hardware structure diagram of a residual strength prediction device for a ceramic matrix composite material in which the residual strength prediction device for the ceramic matrix composite material of the present application is located;

[0030] Figure 8 This is a schematic structural diagram of Embodiment 1 of the residual strength prediction device for ceramic-based composite materials provided in the present application. DETAILED DESCRIPTION

[0031] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.

[0032] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.

[0033] It should be understood that although the terms first, second, third, etc. may be used in the present application to describe various information, these information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Depending on the context, the word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining".

[0034] Specific embodiments are given below to introduce the technical solution of the present application in detail.

[0035] Figure 1 This is a flow chart of Example 1 of the residual strength prediction method of the ceramic matrix composite material provided in this application. Please refer to Figure 1The method provided in this embodiment is used to predict the residual strength of a ceramic matrix composite material under variable amplitude cyclic loading, and the method may include:

[0036] S101. Searching for a target hysteresis modulus degradation model corresponding to a current load level from among the predetermined hysteresis modulus degradation models corresponding to various load levels.

[0037] Specifically, the load level is the load level, and the strength level of the loading can be determined by the load level. It should be noted that the specific number of load levels is set according to actual needs, and is not limited in this embodiment. In specific implementation, multiple different stress levels from low to high can be set as different load levels to comprehensively evaluate the fatigue performance and residual strength changes of the material under different stress conditions.

[0038] Furthermore, the hysteresis modulus degradation model is a mathematical model used to describe the gradual change of the hysteresis modulus of a material as the number of cycles increases during use.

[0039] In specific implementation, the stress and strain data of ceramic-based composite materials at different load levels can be collected through experimental records or real-time monitoring, and the stress ratio of the maximum stress to the minimum stress during loading can be calculated; at the same time, the hysteresis loop of the material under multiple loading cycles can be recorded to obtain the hysteresis modulus of each cycle, and then the obtained stress ratio and hysteresis modulus data can be cleaned and preprocessed to obtain training samples and train the hysteresis modulus degradation model corresponding to each load level.

[0040] It can be understood that each hysteresis modulus degradation model corresponds to a load level. Therefore, after determining the current load level, the corresponding hysteresis modulus degradation model can be directly determined as the target hysteresis modulus degradation model.

[0041] The specific method for determining the hysteresis modulus degradation model will be described in detail in the following embodiments and will not be repeated here.

[0042] S102: Calculate the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model.

[0043] In specific implementation, the current hysteresis modulus may be calculated based on a fourth formula, and the fourth formula is:

[0044]

[0045] Among them, the is the current hysteresis modulus; the m i 、z i 、a i 、b i is the fitting parameter of the target hysteresis modulus degradation model; the n iis the current cycle number.

[0046] Specifically, referring to the formula, two exponential terms are combined when calculating the current hysteresis modulus The complex nonlinear characteristics of the degradation of the hysteresis modulus with the number of cycles can be described by two different exponential terms.

[0047] In specific implementation, the two index terms can reflect different degradation speeds or mechanisms and represent different material fatigue processes. For example, in one embodiment, the first index term represents an initial fast degradation process, and the second index term represents a later slow degradation process.

[0048] It should be noted that the degradation of the current hysteresis modulus is mainly affected by the number of cycles. The current number of cycles n is introduced when calculating the current hysteresis modulus. i , which can dynamically describe the changes in the hysteresis modulus of the material under multiple loadings.

[0049] In specific implementation, the logarithmic form of lg(n i ) characterizes the logarithmic dependence of the fatigue process, so that the degradation rate of the material at different fatigue stages can be flexibly fitted and described.

[0050] Furthermore, by introducing the fitting parameter m of the target hysteresis modulus degradation model i 、z i 、a i 、b i ,Since the target hysteresis modulus degradation model simulates the rate and amplitude of the hysteresis modulus decay at the current load level, the current hysteresis modulus can be determined more accurately.

[0051] The fourth formula can flexibly describe the fatigue degradation process of different materials under different cycle numbers through a double exponential structure. By adapting to different load levels and adjusting the flexible fitting parameters, it can accurately capture the changes in the hysteresis modulus of the material, especially the nonlinear description of the degradation rate in high-cycle and low-cycle fatigue.

[0052] The residual strength prediction method of the ceramic matrix composite material provided in this embodiment captures the complex nonlinear degradation characteristics of the material hysteresis modulus through the two exponential terms of the fourth formula, and combines the fitting parameters of the target hysteresis modulus degradation model to accurately and flexibly determine the current hysteresis modulus. In addition, referring to the previous description, the hysteresis modulus degradation model is separately fitted for the fatigue behavior of different load levels, and each hysteresis modulus degradation model reflects the influence of different stress levels on the hysteresis modulus degradation.

[0053] Figure 2 This is a schematic diagram of the hysteresis modulus shown in an exemplary embodiment of the present application. Figure 2Under variable amplitude cyclic load, the hysteresis modulus corresponding to the three different load levels is continuous. In other words, the hysteresis modulus at the end of the first-level cyclic load cycle is the same as the hysteresis modulus at the beginning of the second-level cyclic load cycle, and the hysteresis modulus at the end of the second-level cyclic load cycle is the same as the hysteresis modulus at the beginning of the tertiary cyclic load cycle.

[0054] S103, determining the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function.

[0055] Specifically, the static strength distribution function is used to describe the strength characteristics of a material under static loading conditions, and various factors of material loading can be fully considered through the static strength distribution function.

[0056] In combination with the above introduction, for example, in one embodiment, the predetermined static strength distribution function is as follows:

[0057]

[0058] Where x is the preset failure stress corresponding to the current load level;

[0059] σ max is the peak load value of the current load level;

[0060] α2 is the shape parameter; β2 is the size parameter.

[0061] It should be noted that the preset failure stresses corresponding to different load levels are set according to actual needs and are not limited in this embodiment. In addition, the preset failure stresses corresponding to different load levels are different.

[0062] In specific implementation, the peak load value of the current load level and the preset failure stress corresponding to the current load level are substituted into a predetermined static strength distribution function to calculate the failure probability corresponding to the current load level.

[0063] S104, calculating the fatigue life of the current load level according to the failure probability, the peak load value, and a predetermined correlation between the fatigue life and the peak load value.

[0064] Specifically, the fatigue life of the current load level is the number of cycles that the material undergoes from the beginning of loading to the occurrence of fatigue failure at this load level.

[0065] Furthermore, the correlation between fatigue life and peak load value can be expressed according to the following formula:

[0066] X r (n i )=σ max,i ;

[0067] Among them, σmax,i is the peak load value of fatigue at level i, X r (n i ) characterizes material failure, n i The current loop number.

[0068] Furthermore, the fatigue life of the material is equal to the sum of the number of fatigue cycles under different load levels, which can be expressed by the following formula:

[0069]

[0070] Where N is the fatigue life, n i The current loop number.

[0071] It can be understood that the correlation between fatigue life and peak load value can be calculated by the above formula.

[0072] Furthermore, the SN curve is used to describe the relationship between the stress level (abbreviated as S) and the number of cycles required to reach fatigue failure (abbreviated as N) under fatigue load. In the SN curve, the stress level is usually used as the horizontal axis and the fatigue life is used as the vertical axis. In specific implementation, the SN curve can be obtained by fitting experimental data.

[0073] It can be understood that the SN curve reflects the fatigue performance of materials under different stress levels and is an important basis for evaluating material fatigue strength, designing fatigue tests, and predicting fatigue life.

[0074] Optionally, in a possible implementation, the fatigue life of the current load level may be calculated based on a third formula, and the third formula is:

[0075] N i =10 Yi ;

[0076]

[0077] Among them, the N i is the fatigue life of the current load level; i is the failure probability; the σ max is the peak load value; A and B are parameters determined by fitting the SN curve of the ceramic matrix composite material; is a shape parameter determined by fitting the distribution function of the fatigue life of the ceramic matrix composite material.

[0078] It should be noted that in this embodiment, the fatigue life of the current load level represented by the logarithm is converted into the actual current fatigue life, and then the fatigue life is calculated by -ln(1-P i) reflects the distribution characteristics of failure probability in the logarithmic domain, combined with A and B enable the fatigue life model to capture the nonlinear degradation characteristics of the material at different stress levels, so that the fatigue life of the current load level can be accurately calculated.

[0079] Specifically, the failure probability describing the failure trend of the material at a specific stress level is calculated through the static strength distribution function and the load conditions, and then when calculating the fatigue life, The nonlinear fatigue degradation characteristics of materials under different failure probabilities are introduced. φ is used as a shape parameter to adjust the sensitivity of failure probability to fatigue life, that is, to adjust the degree of nonlinearity, so as to adapt to the characteristics of different materials. In addition, σ max is the peak load value, which is directly involved in the calculation and describes the positive correlation between the material fatigue life and the peak load. Furthermore, A and B are fitting parameters, which respectively adjust the offset and proportional relationship between the life and the load. The fatigue life can be accurately calculated through the above formula.

[0080] S105. Determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the change law of the fatigue performance of the material from the degradation trend, nonlinear characteristics and stage characteristics during the loading process.

[0081] Specifically, the fatigue degradation factor takes into account all aspects of the material and can more accurately describe the degradation process of material properties.

[0082] In a possible implementation manner, the specific implementation process of this step may include:

[0083] (1) Calculating a current matrix volume fraction of the ceramic matrix composite material according to a current hysteresis modulus of the ceramic matrix composite material, an initial hysteresis modulus of the ceramic matrix composite material, and an initial fiber volume fraction of the ceramic matrix composite material.

[0084] In specific implementation, the current matrix volume fraction can be calculated based on the following formula:

[0085]

[0086] Where V′ is the current matrix volume fraction, is the current hysteresis modulus, E f is the initial hysteresis modulus, V f is the initial fiber volume fraction of the ceramic matrix composite.

[0087] It should be noted that the initial hysteresis modulus E fand the initial fiber volume fraction V of the ceramic matrix composite f It can be measured at the beginning of material operation, and the current hysteresis modulus can be measured experimentally The current matrix volume fraction V′ is calculated.

[0088] (2) Calculating a current hysteresis modulus degradation index based on the current hysteresis modulus, the initial hysteresis modulus, the current matrix volume fraction, the initial fiber volume fraction, and a preset exponential coefficient related to hysteresis modulus degradation; wherein the current hysteresis modulus degradation index focuses on the overall degradation trend of material properties.

[0089] In a specific implementation, the current hysteresis modulus degradation index may be calculated based on a first formula, where the first formula is:

[0090]

[0091] Wherein, T is the current hysteresis modulus degradation index, is the current hysteresis modulus, the E f is the initial hysteresis modulus, V′ is the current matrix volume fraction, and V f is the initial fiber volume fraction, the c i is the exponential coefficient associated with the preset hysteresis modulus degradation.

[0092] Specifically, the preset exponential coefficient related to the hysteresis modulus degradation is used to adjust the nonlinear degree of degradation. i Can reflect the sensitivity of fatigue degradation.

[0093] It can be understood that the current hysteresis modulus degradation index describes the degradation ratio of the hysteresis modulus of the material relative to the initial state, and is used to quantify the impact of the current loading cycle on the material properties. Therefore, the current hysteresis modulus degradation index can directly reflect the performance changes of the material caused by the accumulation of microscopic damage during fatigue loading.

[0094] (3) determining a current cycle loading influence item according to the current cycle number and the current fatigue life; wherein the current cycle loading influence item focuses on the fluctuation caused by the loading cycle and reflects the dynamic influence of the loading cycle on the degradation rate.

[0095] In a specific implementation, the current cycle loading influence term may be calculated based on a second formula, where the second formula is:

[0096]

[0097] Wherein, t is the current cycle loading influence term, Q is a preset constant, ranging from 0 to 0.8, and N iis the current fatigue life, the n i is the current cycle number.

[0098] Specifically, It can be regarded as a regulating factor, reflecting the influence of the current fatigue life.

[0099] It is understandable that in ceramic-based composites, performance degradation will show nonlinear periodic fluctuations with loading cycles. The sine function can well describe this phenomenon. Therefore, the sine function is used to capture the periodic or fluctuating behavior of the material during fatigue loading, reflecting the dynamic influence of loading on the degradation rate.

[0100] It can capture the stage effects of fatigue loading cycles, especially the fluctuations in the degradation rate of materials at different loading stages (such as initial loading, mid-term, and late stages), and provide additional information to reflect the nonlinear and cyclic characteristics of the loading process.

[0101] (4) The product of the current hysteresis modulus degradation index and the current cyclic loading influence term is determined as a fatigue degradation factor; wherein the fatigue degradation factor reflects the change law of the material fatigue performance from the degradation trend, nonlinear characteristics and stage characteristics during the loading process.

[0102] Specifically, by multiplying the current hysteresis modulus degradation index calculated in the above step (3) and the current cyclic loading influence term calculated in step (4), a fatigue degradation factor characterizing the overall degradation degree of the ceramic matrix composite material can be obtained.

[0103] In specific implementation, the fatigue degradation factor can be calculated based on the following formula:

[0104] H = T × t;

[0105] Among them, H is the fatigue degradation factor, T is the current hysteresis modulus degradation index, and t is the current cyclic loading influence term.

[0106] It can be understood that the degradation factor can not only reflect the overall decay of the material with time or increasing number of cycles, but also reflect the nonlinear characteristics during the loading process and the different degradation rates that may be exhibited at different stages, which facilitates the accurate determination of the overall degradation degree of ceramic matrix composites under different conditions and at different stages.

[0107] As described above, the hysteresis modulus degradation index focuses on the overall degradation trend of material properties and is directly related to the change in hysteresis modulus. The current cyclic loading influence term focuses on the periodic or stage fluctuations caused by the loading cycle, reflecting the dynamic impact of loading on the degradation rate. Through the combination of the two terms, the fatigue degradation factor can not only describe the long-term degradation trend of the material, but also capture the nonlinear and stage characteristics during the loading process, thereby more comprehensively reflecting the changing law of the material fatigue performance.

[0108] S106, calculating the strength attenuation value according to the peak load value of the current load level, the residual strength at the last cycle number and the fatigue degradation factor.

[0109] In specific implementation, the intensity attenuation value can be determined based on the following formula:

[0110] σ 衰减 =(σ UTS,i -σ max )(1+H);

[0111] Among them, σ 衰减 is the intensity attenuation value, σ UTS,i is the residual strength under the last cycle number, σ max is the peak load value of the current load level, and H is the fatigue degradation factor.

[0112] S107, calculating the residual strength of the ceramic matrix composite material at the current number of cycles according to the peak load value of the current load level and the strength attenuation value.

[0113] In specific implementation, the residual strength of the ceramic matrix composite material under the current number of cycles can be determined based on the following formula.

[0114] X r,i =σ max +σ 衰减 ;

[0115] Among them, X r,i is the residual strength;

[0116] σ max is the peak load value of the current load level;

[0117] σ 衰减 is the intensity attenuation value.

[0118] It can be understood that by calculating the fatigue degradation factor, the influence of fatigue damage can be fully considered in combination with the hysteresis modulus degradation, the number of cycles and the material properties when predicting the residual strength.

[0119] In addition, referring to the previous description, it can be seen that the probability distribution of the residual strength under variable amplitude conditions is as follows:

[0120]

[0121] Figure 3 This is a schematic diagram of the prediction result of the residual strength shown in an exemplary embodiment of the present application. Figure 3 , from the 1st cycle to the 8000th cycle, the load is constant, and the residual strength change is shown by the red line. From the 8000th cycle to the 1000000th cycle, the residual strength change corresponding to the constant load is shown by the red line, the residual strength change corresponding to the load reduction is shown by the green line, and the residual strength change corresponding to the load increase is shown by the black line. See Figure 3 , using the method provided in this embodiment, the residual strength can be accurately predicted.

[0122] Referring to the previous description, it can be understood that the method provided in this embodiment has at least the following advantages: based on the multi-load hysteresis modulus degradation model, considering the dynamic changes of the number of cycles and the load, the model can carefully characterize the fatigue behavior of the ceramic matrix composite material. The statistical characteristics are introduced by the failure probability and the static strength distribution function, and the prediction accuracy is further improved. In actual engineering, ceramic matrix composite materials are often under variable amplitude loads, and the strength degradation has uncertainty. This method can adapt to the fatigue damage characteristics under variable amplitude loads through multi-load modeling and dynamic calculation. From the initial state to the failure state, the hysteresis modulus, fatigue life, fatigue degradation factor and strength attenuation value are gradually calculated, and the fatigue degradation process of the ceramic matrix composite material is fully characterized. The model can capture the dynamic characteristics of early rapid degradation and late slow degradation, and provide more comprehensive information for engineering design. Combined with the degradation model and parameters determined by experimental data, the prediction results have high reliability and engineering practical value.

[0123] The residual strength prediction method of the ceramic matrix composite material provided in the present embodiment is to find the target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels, and then calculate the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model, and then determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function, and then calculate the fatigue life of the current load level according to the correlation between the failure probability, the peak load value and the predetermined fatigue life and the peak load value, and then determine the fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles, so as to calculate the strength attenuation value according to the peak load value of the current load level, the residual strength under the previous number of cycles and the hysteresis modulus degradation index, and calculate the fatigue degradation factor according to the current load level. The peak load value and strength attenuation value of the level are used to calculate the residual strength of the ceramic matrix composite material under the current number of cycles. The current hysteresis modulus degradation model is found in advance, and then the current hysteresis modulus is calculated based on this, so that the current hysteresis modulus can be accurately calculated. In addition, when calculating the fatigue life of the current load level, the failure probability is introduced so that the calculation of the fatigue life can reflect the influence of the difference in load levels in actual working conditions on the life, and the fatigue life can be accurately calculated. Furthermore, on the basis of the above, the fatigue degradation factor is calculated according to the current hysteresis modulus, the initial volume fraction, the initial hysteresis modulus, the fatigue life and the current number of cycles. The fatigue degradation factor is used to quantify the material strength degradation at different cycle stages, and then the residual strength is predicted based on the fatigue degradation factor. In this way, through the coordinated cooperation of the above steps, the complex degradation behavior of the material under multi-load fatigue is decomposed, modeled and calculated, and the accurate prediction of the residual strength under variable amplitude load conditions is achieved.

[0124] Figure 4 This is a flow chart of Example 2 of the residual strength prediction method for ceramic matrix composite materials provided in this application. Figure 4 Based on the above embodiment, the steps of determining the correlation between the predetermined fatigue life and the peak load value include:

[0125] S401. Fitting the SN curve and fatigue life distribution function of the ceramic matrix composite material according to the fatigue life of the ceramic matrix composite material at different stress amplitudes obtained in fatigue experiments.

[0126] The SN curve describes the fatigue life (N) of a material at different stress amplitudes (S), usually expressed in logarithmic form:

[0127] log N = AB·log S;

[0128] Among them, A and B are fitting constants, S is the stress amplitude, and N is the fatigue life.

[0129] Specifically, the fatigue life data of the ceramic matrix composite material under different peak loads are obtained through experiments. In specific implementation, the fatigue life of the ceramic matrix composite material can be determined under the stress amplitude corresponding to different load levels and characterized by the number of cycles. That is, during the experiment, the fatigue life (N) data under different stress amplitudes (S) are recorded to form a data set, and then the data set is used to fit the SN curve. Furthermore, the distribution function of the fatigue life can be fitted based on the data set.

[0130] For example, in one embodiment, under peak load 1, the fatigue life of the ceramic matrix composite material is 800,000 cycles, under peak load 2, the fatigue life of the ceramic matrix composite material is 80,000 cycles, and under peak load 3, the fatigue life of the ceramic matrix composite material is 8,000 cycles. Based on the experiment, a data set is obtained.

[0131] S402. Determine the correlation between fatigue life and peak load according to the SN curve and the distribution function; wherein the correlation combines the failure probability, peak load and nonlinear fatigue behavior of the material, and expresses the variation law of fatigue life in logarithmic form.

[0132] Specifically, A and B can be determined based on the SN curve, and the distribution function can be used to determine Based on this, the correlation between fatigue life and peak load is obtained, which is as follows:

[0133] N i =10 Yi ;

[0134]

[0135] Among them, the N i is the current fatigue life; the P i is the failure probability; the σ max is the peak load value; A and B are parameters determined by fitting the SN curve of the ceramic matrix composite material; Yi is the fatigue life of the current load level; is a shape parameter determined by fitting the distribution function of the fatigue life of the ceramic matrix composite material.

[0136] The residual strength prediction method of the ceramic matrix composite material provided in this embodiment first fits the SN curve and the distribution function of the fatigue life of the ceramic matrix composite material according to the fatigue life of the ceramic matrix composite material under different stress amplitudes obtained in the fatigue test, and then determines the correlation between the fatigue life and the peak load according to the SN curve and the distribution function. The correlation combines the failure probability, peak load and nonlinear fatigue behavior of the material, and expresses the variation law of the fatigue life in logarithmic form. In this way, the peak load σ max and shape parameters The nonlinear variation of fatigue life can be captured. At the same time, converting fatigue life into logarithmic form helps to capture the nonlinear characteristics of the cumulative effect of failure. Based on this correlation, the fatigue life can be accurately determined.

[0137] Figure 5 This is a flow chart of Example 3 of the residual strength prediction method for ceramic matrix composite materials provided in this application. Figure 5 Based on the above embodiment, the process of determining the hysteresis modulus degradation model corresponding to each predetermined load level includes:

[0138] S501. Constructing an initial hysteresis modulus degradation model; the initial hysteresis modulus degradation model is used to characterize the variation trend of the hysteresis modulus of the ceramic-based composite material with the number of cycles after the ceramic-based composite material undergoes a loading cycle; wherein the initial hysteresis modulus degradation model describes the fatigue degradation process of the material under different numbers of cycles through a double exponential structure.

[0139] Specifically, the initial hysteresis modulus degradation model is a mathematical model used to describe the gradual decrease of the hysteresis modulus of a material with the number of cycles after fatigue loading.

[0140] In this embodiment, the constructed initial hysteresis modulus degradation model is as follows:

[0141]

[0142] in, is the hysteresis modulus; m0, z0, a0, b0 are the unknown parameters to be fitted; n i The current loop number.

[0143] It should be noted that the initial hysteresis modulus degradation model adopts a double exponential form to characterize the nonlinear change trend of early rapid degradation and later slow degradation.

[0144] S502, obtaining stress data and strain data of the ceramic matrix composite material under different load levels.

[0145] Specifically, fatigue experiments are carried out to record relevant data of stress and strain under different load levels.

[0146] In specific implementation, the fixed maximum stress and stress ratio corresponding to each load level can be recorded, and the data obtained from the experimental measurement can be grouped according to the number of cycles, and then the data can be cleaned and preprocessed to remove abnormal data.

[0147] S503 . For each load level, based on the same stress ratio condition, the parameters of the initial hysteresis modulus degradation model are fitted through the stress data and strain data under the load level to obtain the hysteresis modulus degradation model corresponding to the load level.

[0148] In the specific implementation, for the data of each load level, the nonlinear least squares method is used to fit the double exponential model, and m0, z0, a0, and b0 are adjusted to make them more consistent with the experimental data.

[0149] Furthermore, the model is iteratively updated to minimize the error between the hysteresis modulus obtained experimentally and the hysteresis modulus predicted by the initial hysteresis modulus degradation model.

[0150] The residual strength prediction method of the ceramic matrix composite material provided in this embodiment first constructs an initial hysteresis modulus degradation model, and then obtains stress data and strain data of the ceramic matrix composite material under different load levels; finally, for each load level, based on the same stress ratio condition, the parameters of the initial hysteresis modulus degradation model are fitted through the stress data and strain data under the load level to obtain the hysteresis modulus degradation model corresponding to the load level, wherein the initial hysteresis modulus degradation model describes the fatigue degradation process of the material under different numbers of cycles through a double exponential structure; in this way, through the double exponential form, the model can distinguish the stage characteristics of early rapid degradation and late slow degradation, and can reflect the nonlinear attenuation characteristics of the material under high cycle and low cycle fatigue.

[0151] Figure 6 This is a flow chart of Example 4 of the residual strength prediction method for ceramic matrix composite materials provided in this application. Figure 6 Based on the above embodiment, the steps of determining the predetermined static intensity distribution function include:

[0152] S601, obtaining failure strength data of the ceramic matrix composite material when it fails.

[0153] Specifically, the ceramic matrix composite material may be subjected to multiple fatigue tests, and stress data at each failure may be recorded to form a failure strength data set.

[0154] In specific implementation, for example, in one embodiment, after R fatigue tests, the failure strength data formed is {σ fail1 , σ fail2 , σ fail3 , ..., σ failR}.

[0155] S602, assuming that the initial strength distribution of the ceramic matrix composite material obeys a two-parameter Weibull distribution, and based on the failure strength data, fitting to obtain an initial strength distribution function.

[0156] Specifically, the two-parameter Weibull distribution is used to describe the randomness of material strength and fatigue life, and can be characterized by the following formula:

[0157]

[0158] Among them, α2 is the shape parameter, β2 is the scale parameter, and the shape parameter and scale parameter are fitted by failure strength data.

[0159] It should be noted that the shape parameter is used to control the steepness of the curve, and the scale parameter is used to control the level of feature intensity.

[0160] In specific implementation, the failure strength data is input into a two-parameter Weibull distribution function, and the initial strength distribution function is obtained by fitting.

[0161] S603: Modify the initial distribution function to exclude the failure event of the first fatigue cycle.

[0162] In specific implementation, during the fitting process, the first fatigue cycle (ie, n=1) is identified and determined as failed sample data, and these samples are combined to exclude early failures caused by material defects or manufacturing defects.

[0163] Furthermore, after eliminating the failure event of the first fatigue cycle, the Weibull distribution fitting was performed again to obtain the corrected distribution function.

[0164] S604: Determine the corrected distribution function as the static strength distribution function of the ceramic-based composite material.

[0165] Specifically, the modified distribution function has a modified shape parameter and scale parameter, and the re-established static strength distribution function of the ceramic matrix composite material can be expressed by the following formula:

[0166]

[0167] The residual strength prediction method of the ceramic-based composite material provided in the present embodiment first obtains the failure strength data of the ceramic-based composite material when it fails; then assumes that the initial strength distribution of the ceramic-based composite material obeys the two-parameter Weibull distribution, and fits the initial strength distribution function based on the failure strength data; then corrects the initial distribution function to exclude the failure event of the first fatigue cycle; finally, the corrected distribution function is determined as the static strength distribution function of the ceramic-based composite material, so that, on the first hand: through the visualization of the Weibull distribution curve, the failure probability distribution of the material at different strength levels can be displayed, which is convenient for intuitively understanding the strength characteristics of the material; on the second hand: through fitting the experimental data, the static strength distribution function can truly reflect the strength characteristics of the material, exclude the early failure data caused by human errors and material defects, and eliminate the abnormal failure events of the first cycle, so that the fitting is closer to the essential performance of the material; in this way, the static strength distribution function, as an initial strength benchmark, can provide more accurate input for the fatigue life model, and can more accurately predict the failure probability of the material at different load levels.

[0168] Corresponding to the aforementioned embodiment of a method for predicting residual strength of a ceramic-based composite material, the present application also provides an embodiment of a device for predicting residual strength of a ceramic-based composite material.

[0169] The embodiment of the residual strength prediction device for ceramic-based composite materials of the present application can be applied to the residual strength prediction device for ceramic-based composite materials. The device embodiment can be implemented by software, or by hardware or a combination of software and hardware. Taking software implementation as an example, as a device in a logical sense, it is formed by the processor of the residual strength prediction device for ceramic-based composite materials in which it is located reading the corresponding computer program instructions in the non-volatile memory into the memory and running them. From the hardware level, if Figure 7 As shown, it is a hardware structure diagram of the residual strength prediction device of the ceramic matrix composite material in the present application, except Figure 7 In addition to the processor, memory, network interface, and non-volatile memory shown, the residual strength prediction device for ceramic-based composite materials in which the device in the embodiment is located may also include other hardware, which will not be described in detail, generally based on the actual function of the residual strength prediction device for ceramic-based composite materials.

[0170] Figure 8 This is a schematic diagram of the structure of the embodiment 1 of the residual strength prediction device for ceramic matrix composite materials provided in this application. Figure 8 The device provided in this embodiment includes a search module 810, a calculation module 820, a determination module 830 and a processing module 840; wherein:

[0171] The search module 810 is used to search for a target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels;

[0172] The calculation module 820 is used to calculate the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model;

[0173] The determination module 830 is used to determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function;

[0174] The calculation module 820 is used to calculate the fatigue life of the current load level according to the failure probability, the peak load value and the predetermined correlation between the fatigue life and the peak load value;

[0175] The processing module 840 is used to determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the variation law of the fatigue performance of the material from the degradation trend, the nonlinear characteristics and the stage characteristics during the loading process;

[0176] The calculation module 820 is further used to calculate the strength attenuation value according to the peak load value of the current load level, the residual strength under the last cycle number and the fatigue degradation factor;

[0177] The calculation module 820 is further used to calculate the residual strength of the ceramic matrix composite material at the current number of cycles according to the peak load value of the current load level and the strength attenuation value.

[0178] The device of this embodiment can be used to perform Figure 1 The steps, specific implementation principles and implementation processes of the method embodiment shown are similar and will not be repeated here.

[0179] Please continue to refer to Figure 7 The present application also provides a residual strength prediction device for ceramic-based composite materials, comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein when the processor executes the program, the steps of any one of the methods provided in the first aspect of the present application are implemented.

[0180] The present application also provides a computer-readable storage medium having a computer program stored thereon, and when the program is executed by a processor, the steps of any one of the methods provided in the present application are implemented.

[0181] The implementation process of the functions and effects of each unit in the above-mentioned device is specifically described in the implementation process of the corresponding steps in the above-mentioned method, and will not be repeated here.

[0182] For the device embodiment, since it basically corresponds to the method embodiment, the relevant parts can refer to the partial description of the method embodiment. The device embodiment described above is only schematic, wherein the units described as separate components may or may not be physically separated, and the components displayed as units may or may not be physical units, that is, they may be located in one place, or they may be distributed on multiple network units. Some or all of the modules may be selected according to actual needs to achieve the purpose of the present application scheme. A person of ordinary skill in the art can understand and implement it without paying any creative work.

[0183] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for predicting residual strength of a ceramic matrix composite material, characterized in that: The method is used to predict the residual strength of a ceramic matrix composite material under variable amplitude cyclic loading, and the method comprises: Searching for a target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels; Calculating a current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model; Determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function; Calculating the fatigue life of the current load level according to the failure probability, the peak load value and a predetermined correlation between the fatigue life and the peak load value; Determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the change law of the fatigue performance of the material from the degradation trend, the nonlinear characteristics and the stage characteristics during the loading process; Calculate the strength attenuation value according to the peak load value of the current load level, the residual strength at the last cycle number and the fatigue degradation factor; The residual strength of the ceramic matrix composite material at the current number of cycles is calculated according to the peak load value of the current load level and the strength attenuation value.

2. The method according to claim 1, characterized in that The determining of the fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles comprises: Calculating a current matrix volume fraction of the ceramic matrix composite material according to a current hysteresis modulus of the ceramic matrix composite material, an initial hysteresis modulus of the ceramic matrix composite material, and an initial fiber volume fraction of the ceramic matrix composite material; Calculate the current hysteresis modulus degradation index according to the current hysteresis modulus, the initial hysteresis modulus, the current matrix volume fraction, the initial fiber volume fraction, and a preset exponential coefficient related to hysteresis modulus degradation; wherein the current hysteresis modulus degradation index focuses on the overall degradation trend of material performance; Determine a current cycle loading influence item according to the current cycle number and the current fatigue life; wherein the current cycle loading influence item focuses on the fluctuation caused by the loading cycle and reflects the dynamic influence of the loading cycle on the degradation rate; The product of the current hysteresis modulus degradation index and the current cyclic loading influence term is determined as a fatigue degradation factor.

3. The method according to claim 2, characterized in that The calculating the current hysteresis modulus degradation index according to the current hysteresis modulus, the initial hysteresis modulus, the current matrix volume fraction, the initial fiber volume fraction, and a preset exponential coefficient related to hysteresis modulus degradation comprises: The current hysteresis modulus degradation index is calculated based on a first formula, wherein the first formula is: Wherein, T is the current hysteresis modulus degradation index, is the current hysteresis modulus, the E f is the initial hysteresis modulus, V′ is the current matrix volume fraction, and V f is the initial fiber volume fraction, the c i is the exponential coefficient associated with the preset hysteresis modulus degradation.

4. The method according to claim 2 or 3, characterized in that: Determining a current cycle loading influence item according to the current cycle number and the current fatigue life includes: The current cycle loading influence term is calculated based on a second formula, wherein the second formula is: Wherein, t is the current cycle loading influence term, Q is a preset constant, and N i is the current fatigue life, the n i is the current cycle number.

5. The method according to claim 1, characterized in that The calculating the fatigue life of the current load level according to the failure probability, the peak load value and the predetermined correlation between the fatigue life and the peak load value comprises: The fatigue life of the current load level is calculated based on the third formula, and the third formula is: N i =10 Yi ; Among them, the N i is the fatigue life of the current load level; i is the failure probability; the σ max is the peak load value; A and B are parameters determined by fitting the SN curve of the ceramic matrix composite material; is a shape parameter determined by fitting the distribution function of the fatigue life of the ceramic matrix composite material.

6. The method according to claim 1, characterized in that The step of calculating the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model comprises: The current hysteresis modulus is calculated based on the fourth formula, and the fourth formula is: Among them, the is the current hysteresis modulus; the m i 、z i 、a i 、b i is the fitting parameter of the target hysteresis modulus degradation model; the n i is the current cycle number.

7. The method according to claim 1, characterized in that The process of determining the correlation between the predetermined fatigue life and the peak load value includes: According to the fatigue life of the ceramic matrix composite material under different stress amplitudes obtained in the fatigue test, fitting the SN curve and the distribution function of the fatigue life of the ceramic matrix composite material; The correlation between fatigue life and peak load is determined according to the SN curve and the distribution function; wherein the correlation combines the failure probability, peak load and nonlinear fatigue behavior of the material, and expresses the variation law of fatigue life in logarithmic form.

8. The method according to claim 1, characterized in that The process of determining the hysteresis modulus degradation model corresponding to each predetermined load level includes: Constructing an initial hysteresis modulus degradation model; the initial hysteresis modulus degradation model is used to characterize the variation trend of the hysteresis modulus of the ceramic matrix composite material with the number of cycles after the ceramic matrix composite material undergoes a loading cycle; wherein the initial hysteresis modulus degradation model describes the fatigue degradation process of the material under different numbers of cycles through a double exponential structure; Acquiring stress data and strain data of the ceramic matrix composite material at different load levels; For each load level, based on the same stress ratio condition, the parameters of the initial hysteresis modulus degradation model are fitted through the stress data and strain data under the load level to obtain the hysteresis modulus degradation model corresponding to the load level.

9. The method according to claim 1, characterized in that: The process of determining the predetermined static strength distribution function includes: Obtaining failure strength data of the ceramic matrix composite material when it fails; Assuming that the initial strength distribution of the ceramic matrix composite material obeys a two-parameter Weibull distribution, an initial strength distribution function is obtained by fitting based on the failure strength data; Modifying the initial distribution function to exclude failure events in the first fatigue cycle; The corrected distribution function is determined as the static strength distribution function of the ceramic-based composite material.

10. A residual strength prediction device for ceramic matrix composite materials, characterized in that: The device is used to predict the residual strength of a ceramic matrix composite material under variable amplitude cyclic load, and the device comprises a search module, a calculation module, a determination module and a processing module; wherein, The search module is used to search for a target hysteresis modulus degradation model corresponding to the current load level from the hysteresis modulus degradation models corresponding to the predetermined load levels; The calculation module is used to calculate the current hysteresis modulus according to the current number of cycles and the target hysteresis modulus degradation model; The determination module is used to determine the failure probability corresponding to the current load level according to the peak load value of the current load level, the preset failure stress corresponding to the current load level and the predetermined static strength distribution function; The calculation module is used to calculate the fatigue life of the current load level according to the failure probability, the peak load value and the predetermined correlation between the fatigue life and the peak load value; The processing module is used to determine a fatigue degradation factor according to the current hysteresis modulus, the initial volume fraction of the ceramic matrix composite material, the initial hysteresis modulus of the ceramic matrix composite material, the current fatigue life and the current number of cycles; wherein the fatigue degradation factor reflects the change law of the fatigue performance of the material from the degradation trend, the nonlinear characteristics and the stage characteristics during the loading process; The calculation module is further used to calculate the strength attenuation value according to the peak load value of the current load level, the residual strength under the last cycle number and the fatigue degradation factor; The calculation module is further used to calculate the residual strength of the ceramic-based composite material at the current number of cycles according to the peak load value of the current load level and the strength attenuation value.

Citation Information

Patent Citations

  • Method for simulating fatigue hysteresis loop of ceramic-based composite material in high-temperature environment

    CN111339685A

  • Fracture Fatigue Entropy Determination

    US20120084019A1